PENINGKATAN KOMPETENSI PEDAGOGIK GURU PPKN PRODUKTIF DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI IN HOUSE TRAINING (IHT) DI SMAN 2 PAYAKUMBUH - Harlina, Harlina (STKIP Pesisir Selatan, 2017)
Based on the results of observations and supervision conducted by the authors show that the pedagogic competence of teachers in preparing the RPP is still low. The purpose of this study is to describe and obtain information about the pedagogic competence improvement of productive teachers of PPKN in preparing lesson plans (RPP) through In House Training (IHT) In SMAN 2 Payakumbuh. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. Research subjects consist of 4 productive teachers who teach in SMAN 2 Payakumbuh. Research data was collected using obeservation sheets. Data were analyzed using percentages. The results showed that the implementation of In House Training (IHT) can improve teacher pedagogic competence in preparing RPP. This is evidenced by the average value of the initial competence of teachers before the program is 74. Then after IHT activities there is an increase in the cycle I is 78.70 (good) and after that increases in cycle II to 87.56 (very good).